Prevajanje strokovnih besedil v sodobni slovenski družbi oziroma stanje kulture neleposlovnega prevajanja - Ban, Ivo (Mostovi (Ljubljana), 2006)
In this article the author deals with translating non-literary texts as an academic professional activity which, within various forms of each culture, represents one of the most extensive and productive aspects of language activity. The central discussion leads towards the emphases which relate to the delimitations of what is concealed behind the concept of profession, professional translation and the professional translator - in relation to non-literary texts. In the further text, amongst other matters, a comparative description is also given of those attributes of non-literary and literary texts which can be perceived as being either external or internal signals of the professional text.
Keywords: kultura; prevajanje; strokovna besedila